Microbiological reduction of molybdenum to molybdenum blue as a sustainable remediation tool for molybdenum: a comprehensive review - Yakasai, Hafeez Muhammad; Rahman, Mohd Fadhil; Manogaran, Motharasan; Yasid, Nur Adeela; Syed, Mohd Arif; Shamaan, Nor Aripin; Shukor, Mohd Yunus (MDPI, 2021)
Molybdenum (Mo) microbial bioreduction is a phenomenon that is beginning to be recognized globally as a tool for the remediation of molybdenum toxicity. Molybdenum toxicity continues to be demonstrated in many animal models of spermatogenesis and oogenesis, particularly those of ruminants. The phenomenon has been reported for more than 100 years without a clear understanding of the reduction mechanism, indicating a clear gap in the scientific knowledge. This knowledge is not just fundamentally important—it is specifically important in applications for bioremediation measures and the sustainable recovery of metal from industrial or mine effluent. To date, about 52 molybdenum-reducing bacteria have been isolated globally. An increasing number of reports have also been published regarding the assimilation of other xenobiotics. This phenomenon is likely to be observed in current and future events in which the remediation of xenobiotics requires microorganisms capable of degrading or transforming multi-xenobiotics. This review aimed to comprehensively catalogue all of the characterizations of molybdenum-reducing microorganisms to date and identify future opportunities and improvements.